Consumer’s Purchase Intention of Two Wheelers in Nepal - Neupane, Shubankar Sharma; Sawagvudcharee, Ousanee (Nepalese Journal of Management Science and Research, 2019)
This study examines the consumers’ purchase intention of two-wheelers in Nepal 2017/18. The independent were product knowledge, perceived quality, perceived value and perceived risk and the dependent variable was the purchase intention. This study aims to find those independent variables which affect the dependent variable the most. Applying the correlation and the multiple regressions, the study finds that among the multiple independent purchase intention variables taken for analysis: perceived quality and perceived value affected the dependent variable purchase intention the most. Perceived Quality and Perceived Value have a statistically significant positive relationship with the dependent variable Purchase Intention .The Product Knowledge and mitigated Perceived Risk, on the other hand, had no significant relationship with the dependent variable purchase intention.Therefore, two-wheeler manufacturers in Nepalese context must attempt to improve perceived quality and perceived value in the mind of customers to ensure sales better than their competitors.